DESIGN OF ROV STRAIGHT MOTION CONTROL USING PROPORTIONAL SLIDING MODE CONTROL METHOD - Yudianto, Firman; Herlambang, Teguh; Susanto, Fajar Annas; Suryowinoto, Andy; Tomasouw, Berny Pebo (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
The development of underwater defense technology is commonly related to its usage for security and defense of a country. The need of NKRI (the Republic of Indonesia) for an applicable and multifunctional technology for highly improved unmanned submarines is urgent considering the current necessity of unmanned technology modernization functioning as The Main Weapon System Equipments (ALUTSISTA) to be applied as a spy technology or automatic weapon. This paper focus is on a motion control system design with the motion equation of 2 Degree of Freedom (DOF) applied to an unmanned submarine system or also called a Remote Operated Vehicle (ROV). ROV requires a control system to control its maneuvering motion when underwater, especially in a straight line motion. The ROV motion equation of 2-DOF consisting of surge and roll motions is in the form of a nonlinear equation. The system control design applied to the ROV system used the Proportional Controller method combined with Sliding Mode Control. The simulation results of the Proportional SMC control system with the motion equation of 2-DOF on the ROV system show that the system is stable with an accuracy of surge and roll motions of 95% - 99%.